Enhancing the performance of porous rice husk silica through branched polyethyleneimine grafting for phosphate adsorption - Suzaimi, N.D. (Elsevier B.V., 2020)
Removal of phosphate is necessary to prevent eutrophication and remediate other environmental issues. In this study, branched polyethyleneimine (bPEI) was grafted onto rice husk porous silica (RSi-bPEI) to enhance the selective adsorption of phosphate. The adsorption tests for phosphate were performed at various conditions to assess the effects of pH, dose, initial concentration, and contact time. As confirmed by FTIR-spectra, it was proposed that phosphate species anchored onto RSi-bPEI through ion-exchange and hydrogen bonding. The increase in positive charge of RSi-bPEI, which was due to the presence of protonated amine, played a key role in offering more adsorption sites to augment the adsorption by means of electrostatic attraction. Consequently, RSi-bPEI exhibited qm of 123.46 mg gâ1, which was two-fold better than that of RSi. The adsorption behavior was best described by Langmuir isotherms and the pseudo-second-order kinetics model. Based on the competitive study, the co-existing anions did not interfere with adsorption due to the fact that phosphate could form both inner and outer sphere complexes. In addition to the high performance, high efficiency in wide pH range as well as good stability and easy recyclability are the other promising criteria of RSi-bPEI that promote its practical usage in treating phosphate-induced eutrophication of water bodies. Â© 2020